Strategi Efisiensi Pembiayaan Langganan Daya dan Jasa di Madrasah Ibtidaiyah: Studi Kasus MI Mathlabul Ulum - Umam, Zafilul; Aziz, Abdul (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2025)
This study explores the financial efficiency strategies employed by Madrasah Ibtidaiyah (MI) in managing subscription-based utility and service costs, with a case study at MI Mathlabul Ulum in Sumenep, East Java. Using a qualitative field research approach, data were collected through interviews and direct observation to examine the school's management of electricity, water, internet, and cleaning services. The findings reveal several key challenges: heavy dependence on BOS (School Operational Assistance) funds, lack of real-time energy monitoring systems, absence of periodic service evaluations, and limited managerial capacity among school leaders. Despite these issues, incremental improvements such as LED usage and service price negotiation have begun to emerge. The study concludes that structured financial planning, implementation of monitoring systems, and capacity-building for school administrators are critical for improving cost efficiency and ensuring the sustainability of educational services. The research highlights the urgent need for Madrasah Ibtidaiyah to adopt strategic financial management practices in order to enhance the quality and competitiveness of Islamic primary education in Indonesia.